Enhancing Performance of Anode-Free Li-Metal Batteries by Addition of Ceramic Nanoparticles: Part I. Issue 9 (20th September 2021) - Mukra, Tzach; Marrache, Roy; Shekhter, Pini; Peled, Emanuel
Abstract : Because of their higher energy density, compared to lithium-ion batteries, rechargeable lithium-metal batteries (LMB) have been considered one of the most attractive next-generation energy-storage systems. A promising approach to improve LMB performance, that has gained interest in recent years, is the use of anode-free lithium-metal batteries (AFLMB). Such battery configuration enables elimination of the problem of using excessive amounts of lithium in LMBs, hence increasing the specific energy of the battery. In this work we studied the effect of adding nanoscale ceramic oxides in carbonate-based electrolytes on the cycling performance of the cell and on its anodic SEI properties. The oxides studied were Al2 O3, TiO2 and SiO2 . It was found that the nanoparticle oxide additives significantly improve the coulombic efficiency (CE) and the capacity retention (CR). TiO2 and Al2 O3 presented typical performance with CE of 99.4% and 98.8% and CR of 70% after 36 and 39 cycles, respectively. XPS and EIS measurements were also conducted and showed the superiority of the addition of nanoparticle oxides.